(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The present research, carried out in Gowa Regency, Indonesia, examines the incorporation of indigenous knowledge into participatory development interventions, with a specific emphasis on the perceived advantages associated with this integration. The study of qualitative data yielded four prominent themes, namely "Cultural Preservation," "Sustainable Practices," "Community Empowerment," and "Environmental Impact." The advantage of "Cultural Preservation" was found to be often mentioned, highlighting the community’s dedication to protecting its cultural legacy. The significance of "Sustainable Practices" was underscored as a crucial component for environmentally aware agricultural practices and the promotion of sustainable development. The significance of "Community Empowerment" in promoting active community engagement and the good environmental impact of "Environmental Impact" were both acknowledged. The aforementioned results highlight the many benefits of integrating local knowledge and skills into development processes, with a particular emphasis on the preservation of cultural heritage, the empowerment of communities, the promotion of sustainability, and the enhancement of environmental well-being. Recognizing these advantages may assist stakeholders in the process of choosing culturally suitable and environmentally sustainable development initiatives. This study enhances the comprehension of the significance of local knowledge in participatory development and advocates for more research and cooperation to strengthen community-led advancement.